Proper placement of the Escherichia coli division site requires two functions that are associated with different domains of the MinE protein. - Zhao, C R (1995)
The proper placement of the Escherichia coli division septum requires the MinE protein. MinE accomplishes this by imparting topological specificity to a division inhibitor coded by the minC and minD genes. As a result, the division inhibitor prevents septation at potential division sites that exist at the cell poles but permits septation at the normal division site at midcell. In this paper, we define two functions of MinE that are required for this effect and present evidence that different domains within the 88-amino acid MinE protein are responsible for each of these two functions. The first domain, responsible for the ability of MinE to counteract the activity of the MinCD division inhibitor, is located in a small region near the N terminus of the protein. The second domain, required for the topological specificity of MinE function, is located in the more distal region of the protein and affects the site specificity of placement of the division septum even when separated from the domain responsible for suppression of the activity of the division inhibitor.